Answer:
see explanation
Step-by-step explanation:
- g + 2(3 + g) = - 4(g + 1) ← distribute parenthesis on both sides
- g + 6 + 2g = - 4g - 4 , that is
g + 6 = - 4g - 4 ( add 4g to both sides )
5g + 6 = - 4 ( subtract 6 from both sides )
5g = - 10 ( divide both sides by 5 )
g = - 2
As a check
Substitute g = - 2 into the equation and if both sides are equal then it is the solution.
left side = - 2 + 2(3 - 2) = 2 + 2(1) = 2 + 2 = 4
right side = - 4(- 2 + 1) = - 4(- 1) = 4
Since both sides are equal then g = - 2 is the solution